How ICTs are shaping sustainable and modern farming systems in India - Gakhar, Shalini; Rai, Anil; Sharma, Sheetal (CGIAR Initiative on Digital Innovation, 2024)
Advances in the field of Information and Communication Technology (ICT) are having a profound impact on the agricultural sector. After reaping the benefits of the Green Revolution, we are now poised to witness a new transformation through cutting-edge technologies of ICT, such as artificial intelligence (AI), the internet of things (IoT), robotics, edge computing, big data analytics, unmanned aerial vehicles (UAV), the blockchain, and remote sensors. ICT provides innovative solutions that boost efficiency, productivity, transparency, quality, profitability, and sustainability in farming practices. The value of the digital agriculture market was estimated to be USD 24.2 billion in 2024, and predicted to reach USD 39.8 billion in 2029, according to MarketsandMarkets